Introducing an Analytical Lens to Investigate the Normative Dynamics Between International Law and the 2030 Sustainable Development Goals - Guiry, Niamh (The Opole Studies in Administration and Law, 2024)
The conceptualisation of sustainable development has evolved from a seemingly ambiguous term to a focused suite of non-binding global objectives known as the Sustainable Development Goals (SDGs). The relationship between the SDGs and related subfields of international law could be taken as an example of a novel regime interaction, but how can one theorise and decipher the normative interactivity that may be taking place? Building upon the work of Oran R. Young concerning institutional linkages in international society, this article introduces an analytical lens through which the SDG-international law interconnections can be analysed. The following six types of ‘institutional linkages’ are used to explore and elucidate the potential normative effect of the SDGs on the elaboration, implementation, and interpretation of international law: 1) Embedded, 2) Nested, 3) Clustered, 4) Overlapping, 5) Negating, and 6) Sectional.